Similarity of drinking water biofilm microbiome despite diverse planktonic water community and quality - Slater, Frances C.; Fish, Katherine E.; Boxall, Joby B. (Frontiers in Microbiology, 2025)
The impact of drinking water quality, in particular the planktonic microbiome, on the bacterial and fungal community composition of biofilms in drinking water infrastructure is explored. Understanding drinking water biofilms is critical as biofilms can degrade water quality and potentially present a public health risk if pathogens are released. Biofilms were developed for 12 months in three state-of-the-art pipe loop facilities installed at water treatment works and hence supplied by distinct treated drinking water and unique planktonic bacterial and fungal microbiomes. Each pipe loop had identical physical conditions, including pipe diameter, material and hydraulic regime (shear stress and turbulence). Despite the different bulk-waters, the bacterial and fungal community composition of the biofilm within each loop were remarkably similar, although in different quantities. The similarity between the biofilms from unique systems, with significantly different planktonic microbiomes, suggests shared selective pressures across the different sites which are independent of the varying water qualities, including planktonic community. This suggests that taking a global view of biofilm microbiome management is potentially feasible and that approaches controlling material or hydraulics may be best way to do this.